The Effect of Financial Performance, Fraudulent Statement and Company Size on Costs of Equity - Ina Mutmainah (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
The Company will determine the capital to be spent to make their investment. Capital needed costs called cost of capital as a consequence of the company's capital gains that can come from both internal and external . The capital costs incurred by the company is closely linked with the risk of errors in financial reporting information. This study tries to analyze the influence of the profitability, leverage, fraudulent statement, company size, on the cost of equity. The research was conducted during the period 2016-2018 in the manufacturing companies listed in Indonesia Stock Exchange. Researchers collected data by technical documentation which is currently processing using SPSS 23. By purposive sampling, researchers have collected 45 samples from 15 manufacturing companies that fit the criteria of research. The analytical method used is multiple linear regression with classical assumption including normality test, multicollinearity, heterokedasitas, and autocorrelation. The dependent variable is the cost of equity, and the independent variable is profitability, leverage, fraud, company size. From these results, profitability, leverage, fraud, company size, effect simultaneous to the cost of equity in manufacturing companies in the period 2016-2018. Partially, company size and profitability of a significant effect on the cost of equity, while fraud and leverage do not significantly affect the cost of equity in the companies listed in Indonesia Stock Exchange 2016-2018